Investigation of olive leaf extract as a potential environmentally-friendly corrosion inhibitor for carbon steel - Sherifa Elhady; Hatice Inan; Mahmoud Shaaban; Irene S. Fahim (Scientific Reports, 2023)
Abstract Corrosion constitutes a significant issue in industries that handle metals. Corrosion inhibitors with a low impact on the environment provide a significant economic benefit in various engineering applications. In this work, the effectiveness of olive leaves extract is evaluated as a cost-effective and environmentally-friendly corrosion inhibitor. The corrosion of carbon steel in different concentrations of hydrochloric acid (0.1, 1.0, and 2.0 M) when protected by an aqueous solution of olive leaf extract of concentrations ranging from 10 to 60 ppm is investigated. A green extraction process based upon water extraction is used to ensure minimum impact on the environment. Results show that the corrosion inhibition efficiency increased as the concentration of the olive leaf extract increased. An analysis of variance showed a significant effect of acidic molarity, temperature, and inhibitor concentration on the corrosion rate. A significant statistical model indicates that the inhibitor exhibits higher efficiencies at higher acidic molarity. Results of SEM and EDX also demonstrated that a protective film of the inhibitor on the specimen surface plays a role in corrosion inhibition, suggesting that the inhibitor molecules are adsorbed at the interface between the carbon steel and the acid solution. The study provides an insight on the corrosion mechanism and highlights the potential of olive oil extract as an eco-friendly alternative to traditional corrosion inhibitors.